2020
DOI: 10.9734/ajacr/2020/v7i230178
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of 40 Plants of the Senegalese Flora, an Important Therapeutic Diversity for Populations

Abstract: Diabetes mellitus is group of a metabolic desorder caused by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. It is a major public health problem in all countries of the world. In Africa, it was predicted that the continent, will see the greatest increase, from 19 millions in 2019 to 47 million diabetics in 2045. In the absence of sufficient public health care coverage and the high cost of modern medicine, major part of the population of developing countries turns to traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Few studies have evaluated the antidiabetic property of Detarium senegalense; its blood glucose lowering potency and its metabolic effects on various organ systems [3]. A study specific (for example) to its reduction capability on blood glucose via the metabolic pathway was carried out by David et al, [4].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the antidiabetic property of Detarium senegalense; its blood glucose lowering potency and its metabolic effects on various organ systems [3]. A study specific (for example) to its reduction capability on blood glucose via the metabolic pathway was carried out by David et al, [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of these species, Vernonia colorata (Willd.) Drake, a shrubby plant of 3 to 4 meters high, is widespread in countries such as Burkina, Mali, Togo, Benin, Senegal and Cameroon [2]. It is used there for the treatment of fever, gastritis, jaundice, arterial hypertension, general tiredness, yellow fever [3,4] and in the human food.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the decoction of stem, root and trunk barks of Vernonia colorata are used in the treatment of schistosomiasis, sterility and frigidity [6]. In the Center region of Burkina Faso, for example, ethnobotanical surveys showed that Vernonia colorata is among the species most used for the traditional treatment of certain infectious diseases such as malaria, stomach ailments, and diseases of the skin [3,7].Others studies have shown that Vernonia colorata macerates leaf have various pharmacological activities such as antidiabetic, antioxidant, antitumor, anti-inflammatory, diuretic, antihypertensive, ant plasmodium, hypoglycemic and analgesic [2,3,7,8,9] However, few scientific data exists on the pharmacological properties of Vernonia colorata, particularly on the toxicity of the aqueous extract. The aim of this study is to highlight the phytochemical constituents and to study the acute and subacute toxicities of the aqueous extract of leaves of Vernonia colorata (AEVC) in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…The distressing statistics of damage that diabetes could cause, necessitate to identify and explore new avenues for diabetes management from natural products having fewer side effects. Indeed, the use of plants in the management of several pathologies such as diabetes no longer needs to be demonstrated [5,6]. According to Saravanan et al, traditional Medicine preparations could be a potential source of novel antidiabetic compounds or phytomedicines supplements.…”
Section: Introductionmentioning
confidence: 99%